Chekhov’s 'Little Woman': Exploration of Gender Roles and Family Values in 19th Century Literary Traditions - Dimitruk, Elena; Buchelnikova, Anna; Indarti, Titik; Pairin, Udjang (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2025)
This study examines the representation of the